1998
DOI: 10.1111/j.1600-0714.1998.tb02094.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of growth potential by MIB‐1 immunohistochemistry in ameloblastic fibroma and related lesions of the jaws compared with ameloblastic fibrosarcoma

Abstract: Sano K, Yoshida S, Ninomiya H, Ikeda H, Ueno K, Sekine J, Iwamoto H, Uehara M, Inokuchi T: Assessment of growth potential by MIB‐1 immunohistochemistry in ameloblastic fibroma and related lesions of the jaws compared with ameloblastic fibrosarcoma. J Oral Pathol Med 1998; 27: 59–63. © Munksgaard, 1998. Specimens from two ameloblastic fibromas (including one recurrent case), two ameloblastic fibro‐odontomas, and one ameloblastic fibrosarcoma were subjected to investigation by MIB‐1 immunohistochemistry in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 14 publications
4
22
1
3
Order By: Relevance
“…When Ki-67 was quantified, positivity rates ranged from 13.5% to 60.0% for the malignant mesenchymal component. Although no established cutoff value for Ki-67 positivity has been reported in the literature, the present case is within the interval of Ki-67 expressed in malignant lesions (~20.0%), suggesting that proliferative factors, in association with histopathological features, may be useful markers for the identification of malignant cases (4,5,69,79,88,89,113).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…When Ki-67 was quantified, positivity rates ranged from 13.5% to 60.0% for the malignant mesenchymal component. Although no established cutoff value for Ki-67 positivity has been reported in the literature, the present case is within the interval of Ki-67 expressed in malignant lesions (~20.0%), suggesting that proliferative factors, in association with histopathological features, may be useful markers for the identification of malignant cases (4,5,69,79,88,89,113).…”
Section: Discussionmentioning
confidence: 50%
“…The search strategy resulted in the identification of 119 cases in 88 articles (4-6,9-13, 113 disease; the remaining patients (6/8) had no evidence of disease at the last recorded appointment. Only two cases were diagnosed with AFDS, (13,45) and both involved the posterior mandibles of non-white male patients in the third decade of life (mean, 26±1.4 years).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is usually a juxta epithelial hyalinization around those islands signifying the process of epithelial mesenchymal interaction [17] . Immunohistochemical markers like proliferating cell nuclear antigen (PCNA) and MIB-1 has been studied where it was found that MIB-1 has been expressed in the mesenchymal component suggesting the higher labeling indices in the Mesenchymal component rather than the epithelial component [18,19] . The role of these markers helped in understanding the growth and aggressive potential of the tumours.…”
Section: Ameloblastic Fibroma-mentioning
confidence: 99%